The Role of Inflammation and Oxidative Stress in the Etiology of Polycystic Ovary Syndrome: A Review Article - Nahid Nasiri; Arezoo Arabipoor; Poopak Eftekhari-Yazdi (Mashhad University of Medical Sciences, 2023)
Introduction: In recent years, the role of inflammation and oxidative stress in the etiology of polycystic ovary syndrome has received more attention. Evaluation of the existing studies regarding the effects of inflammatory mediators and oxidative stress on ovarian function in patients with polycystic ovary syndrome (PCOS) indicates the key role of these factors in the progress and development of disease complications. The current review study was conducted with aim to summarize the presence and role of the aforementioned inflammatory mediators as well as the effect of recent treatment approaches including the use of antioxidant supplements and anti-inflammatory agents in improving the results of infertility treatment cycles in these patients.Methods: In the present review article, to find the related articles, databases of PubMed, Science Direct, Scopus, and Google Scholar databases were searched with the keywords of polycystic ovary syndrome, inflammation, oxidative stress, oxygen-free radicals, antioxidant supplementation, infertility treatment, androgens, cytokines, and insulin resistance using the "AND" and "OR" operators from January 1991 to December 2020. Results: After reviewing all the articles in this field, it was found that PCOS, as a genetic and autoimmune disease, is associated with low degrees of inflammation, which plays an important role in the etiology, progression and occurrence of the disease. Moreover, ovulatory dysfunction, increased concentrations of oxygen free radicals in granulosa cells, as well as the follicular fluid of infertile PCOS patients under ART treatment, have been reported.Conclusion: It seems that the coordination between three main factors, namely high dietary carbohydrate intake, insulin resistance, and hyperandrogenism, can be considered as the initiator for inflammation induction and oxidative stress in PCOS patients. The antioxidant supplements and anti-inflammatory agents can be useful to improve the results of infertility treatment cycles in these patients; however, concluding the results still requires further studies.